2022
DOI: 10.1007/s10652-022-09845-6
|View full text |Cite
|
Sign up to set email alerts
|

Lock-release gravity currents propagating over roughness elements

Abstract: The influence of bottom roughness on the development of lock-release gravity currents is investigated through laboratory experiments using Particle Image Velocimetry. The bottom roughness is represented by arrays of vertical LEGO bricks with a constant spacing while varying $$\lambda $$ λ , the relative height of the roughness elements to the gravity current depth. Depending on $$\lambda $$ λ , the roughness elements may affect the gravity current pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…Where partitions were created from the raging columns of the Kelvin-Helmholtz instabilities in the denser fluid. We can now comfortably state that the various behaviours as observed here in this paper also correspond to some of the earlier experimentally studied cases by [6,11,19,20,25,26]. That the instantaneous release of the two fluids after gate was removed led to an initial adjustment phase where the advancing head varies with approximately constant velocity.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Where partitions were created from the raging columns of the Kelvin-Helmholtz instabilities in the denser fluid. We can now comfortably state that the various behaviours as observed here in this paper also correspond to some of the earlier experimentally studied cases by [6,11,19,20,25,26]. That the instantaneous release of the two fluids after gate was removed led to an initial adjustment phase where the advancing head varies with approximately constant velocity.…”
Section: Resultssupporting
confidence: 86%
“…This was the phase we observed much of the Kelvin-Helmholtz instabilities at the interaction layer that was responsible for the partitions in the denser fluid. The overall behaviour as observed here in this investigation might be as a result of the Even though the choice of numerical parameters (Reynolds number 50) for a laminar flow was suggested and ideal for the purpose of this work [6,11,25]. It is worth emphasising that in most of the lock-exchange experimental cases, salt is mostly used to create the density difference.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…There has been a growing interest in understanding the impact of bottom roughness (Nogueira et al, 2013(Nogueira et al, , 2014Cenedese et al, 2016bCenedese et al, , 2018Tanino et al, 2005;Zhang and Nepf, 2008;Bhaganagar and Pillalamarri, 2017;Wilson et al, 2017;Jiang and Liu, 2018;Xu et al, 2019;Zhou and Venayagamoorthy, 2020;Maggi et al, 2022) and isolated obstacles (Tokyay, T., andConstantinescu, G. 2015, de Falco et al 2021) on gravity current propagation. In particular, the presence of rectangular obstacles was shown to increase entrainment as the GC propagates downstream (Wilson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, different bed roughnesses were tested by Nogueira et al (2013) and they found that diverse granular media play an important role in the current dynamics, especially because the extra drag at the bed decreases the front velocity (Nogueira et al, 2013). Bottom roughness has been experimentally idealized by different arrangements of rigid cylinders by Cenedese et al (2016bCenedese et al ( , 2018 and Maggi et al (2022). The former measured density fields and found entrainment enhancement by different processes depending on the configuration of the cylinders, while the latter found that the relative height of the cylinders to the gravity current depth controls the structure and propagation speed of the current with higher roughness elements generating strong recirculation areas between cylinders that interact and modify the overlying current.…”
Section: Introductionmentioning
confidence: 99%